State of food security & nutrition in Bangladesh 2010 - Helen Keller International (HKI) and James P Grant School of Public Health (JPGSPH). (BRAC University, 2011)
Food Security and Nutrition Surveillance Project Report; Lead Analyst and Writer: Jillian L. Waid Editor in Chief: Alayne Adams; Other Contributors: Feroz Ahmed, Lutfa Ashraf, Tanzina Chowdhury, Timothy Evans, Showkat Gani, Abdul Kader, Diane Lindsey, and Akoto Osei.